PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA SEKOLAH DASAR DI KELAS V - Priyatni Priyatni Priyatni; Tati Rubianti; Nelis Supriati (COLLASE (Creative of Learning Students Elementary Education), 2019)
The research is motivated by the low level of students understanding the material concepts well. The study aims to obtain an overview of the achievement and improvement of the mathematical understanding abilities of elementary students who receive learning using the Problem Based Learning (PBL) method compared to students who use ordinary learning. The usual learning in this study is to use the Discovery Learning Method. The research method used in this study is a quasi-experimental method with Control Group Design Pretest designs. The population taken is all elementary school students in the city of Bandung. As for the sample from this study were students of SDN Cihaurgeulis class 5A which amounted to 30 people as the control class and 5B which amounted to 30 people as the experimental class. The instrument used in this study is a description of 7 questions. Data analysis was carried out quantitatively, the data was taken from the results of the Pretest, Post-test to see normalized gain differences. In calculating instrument testing and data processing using Microsoft Excel 2010 and SPSS 23 programs. Postes data analysis to see differences in the average achievement of learning outcomes between sample groups. Based on the results of the study obtained: Achievement Improved ability to understand mathematical concepts of students whose learning using Problem Based Learning is better than those who use ordinary learning.